The Association of Respondent Characteristics with Hyperglycemia among Obesity at the Outpatient Clinic - Aditya, Martanty; Nugraha, Dhanang Prawira; Zita, Hestyana; Yanuar, Michael Resta Surya; Afthoni, Muhammad Hilmi (MPI (Media Pharmaceutica Indonesiana), 2025)
The prevalence of obesity continues to increase and has become one of the significant risk factors for insulin resistance. This condition contributes to the rising prevalence of diabetes mellitus and various metabolic disorders. This study aimed to investigate the association between risk factors andblood glucose levels in individuals with obesity. The respondents were individuals with obesity who had existing medical records and subsequently registered at the outpatient clinic of IHC Lavalette Hospital, Malang. This research employed an observational study design with a cross-sectional method. Sampling was conducted using purposive sampling based on inclusion criteria, resulting in 121 respondents. Data were collected through interviews and medical records and analysed using Fisher exact test. The results showed that certain risk factors were significantly associated with the occurrence of hyperglycemia, including male (OR = 8.376; 95% CI: 1.619–83.695), age 51–75 years (OR = 10.283; 95% CI: 1.979– 102.917), and not taking OADs (OR = 8.426; 95% CI: 1.855–52.901). No significant associations were observed for employment status, marital status, family history of diabetes mellitus, sleep habits, or class I and II obesity. Results related to comorbidity and several odds ratio estimates had wide confidence intervals, reflecting uncertainty due to the small number of cases. Further studies with larger sample sizes are warranted.